Glandular Odontogenic Cyst: a Case Report and Literature Review - Romario Gorgis; Søren Aksel Christian Krarup; Jesper Reibel; Sven Erik Nørholt (eJournal of Oral Maxillofacial Research)
Background: The glandular odontogenic cyst is now a well-known entity comprising < 0.5% of all odontogenic cysts with a recent review tabulating about 200 cases in the English literature. Glandular odontogenic cyst shows epithelial features that simulate salivary gland or glandular differentiation. The importance of glandular odontogenic cyst relates to the fact that it has a high recurrence rate and shares overlapping histologic features with central mucoepidermoid carcinoma. The purpose of this paper is to describe the clinical, radiological, and histopathological features of a case of glandular odontogenic cyst with the course of treatment and 9-years follow-up, followed by a review of the literature.